2005
DOI: 10.1128/mcb.25.24.10711-10720.2005
|View full text |Cite
|
Sign up to set email alerts
|

An eh1-Like Motif in Odd-skipped Mediates Recruitment of Groucho and Repression In Vivo

Abstract: Drosophila Groucho, like its vertebrate Transducin-like Enhancer-of-split homologues, is a corepressor that silences gene expression in numerous developmental settings. Groucho itself does not bind DNA but is recruited to target promoters by associating with a large number of DNA-binding negative transcriptional regulators. These repressors tether Groucho via short conserved polypeptide sequences, of which two have been defined. First, WRPW and related tetrapeptide motifs have been well characterized in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 64 publications
2
59
0
Order By: Relevance
“…5 H and I). The requirement for two dMycbinding sites with Gro is unlike the single-domain protein interactions reported for Engrailed-Gro and Hairy-Gro through Gro's WD domain (21,22).…”
Section: Dmyc and Gro Form A Complex In Vivo And In Vitromentioning
confidence: 60%
“…5 H and I). The requirement for two dMycbinding sites with Gro is unlike the single-domain protein interactions reported for Engrailed-Gro and Hairy-Gro through Gro's WD domain (21,22).…”
Section: Dmyc and Gro Form A Complex In Vivo And In Vitromentioning
confidence: 60%
“…For example, the work on TLE1 used in vitro assays with bacterially derived proteins, which might lack important modifications necessary for binding to the eh1 motif. Indeed, a previous study has shown that the phosphorylation state of S/T residues next to the initial phenylalanine in an eh1 motif has an influence on the interaction with Groucho (Goldstein et al, 2005) and we have previously described a double casein kinase I phosphorylation site that overlaps with the N-terminal eh1 motif (Regad et al, 2007). TLEs can also be post-translationally modified, for example by hyperphosphorylation, which is also induced by the presence of FoxG1 (Buscarlet et al, 2008;Nuthall et al, 2002;Nuthall et al, 2004), or by sumoylation (Ahn et al, 2009).…”
Section: The N-terminal Eh1 Motif Is Important For Physical Associatimentioning
confidence: 99%
“…Since amino acids F and S of the Msx Eh1 motif are required for its interaction with Groucho/TLE family members (Takahashi et al, 2008;Rave-Harel et al, 2005;Goldstein et al, 2005), they were replaced by G and A in Msx1 (Msx1*) and Msx2 (Msx2*) to abolish their repressive activity (Fig. 5Dc).…”
Section: Loss Of Msx1 and Msx2 Functions Alters Interneuronal Differementioning
confidence: 99%